3-DIMENSIONAL STRUCTURE OF CAT MUSCLE PYRUVATE-KINASE AT 6 A RESOLUTION - Stammers, D; Muirhead, H (1975)
A 6 Å resolution electron density map of cat muscle pyruvate kinase has been calculated. From this map it has been possible to isolate a single molecule and to assign subunit boundaries. The binding of substrates, products and the divalent metal cation has been studied. © 1975.